Elaboración de postres asiáticos utilizando como alternativa gastronómica el taxo y la guayaba en cocina creativa - Gudiño Castillo, Cindy Joelle (2024)
The taxo and guava possess a high gastronomic potential that has not yet been fully explored. The aim of this research is to develop a variety of creative Asian desserts using taxo and guava, through the creation of a recipe book, to enrich the culinary offerings and promote a gastronomic fusion. A mixed-method approach was used to analyze culinary practices and collect quantitative data on ingredient proportions. Traditional pastry recipes from five Asian countries—Taiwan, Thailand, China, South Korea, and Japan—were selected, and innovative variants incorporating taxo and guava were developed. The study focused on evaluating the organoleptic properties of taxo and guava, such as their flavor, aroma, texture, and appearance, to determine their viability in creative cuisine. The adaptations included the integration of these fruits in fillings, doughs, sauces, and as base fruits. The results showed that taxo and guava not only maintained but also enhanced the cultural and aesthetic characteristics of Asian desserts, offering freshness and creativity without compromising their cultural authenticity. Guava stood out as a firm and sweet filling, while taxo provided acidity and a distinctive aroma in doughs and sauces. Additionally, a detailed digital recipe book was created, and the desserts were validated through tastings with experts, who positively evaluated the integration of these ingredients. The existing problem is based on the lack of fusion between Ecuadorian products and Asian desserts, which results in a repetitive and uninnovative offering. This research addresses that gap by demonstrating the potential of taxo and guava to innovate in Asian cuisine, promoting sustainable and creative culinary practices. The results demonstrate the versatility of taxo and guava, offering new fusion opportunities and increasing the acceptance of these desserts among Ecuadorian palates.